Mental toughness and choking susceptibility in athletes - Thiessen, Burgandy; Blacker, Mishka; Sullivan, Philip (Frontiers in Psychology, 2024)
Choking susceptibility refers to the propensity of an athlete to choke under pressure. Mesagno has operationalized choking susceptibility as a combination of scores on self-consciousness, anxiety and coping. Despite the potential of Mesagno’s protocol, there is currently limited support for its validity. Secondly, although mental toughness (MT) has a relationship with sport performance, there is limited research on its relationship to choking under pressure, specifically. The current study investigated the relationship between choking susceptibility and mental toughness. It was hypothesized that choking susceptible athletes will have significantly lower levels of mental toughness than those who are not choking susceptible. Data from a heterogeneous sample of athletes (N = 415) was obtained through a Qualtrics research panel. Results of a Mann–Whitney U showed that self-reported mental toughness was not significantly different in athletes categorized as choking susceptible and non-choking susceptible. Correlational analyses also highlighted differences between mental toughness and the composite scores of choking susceptibility, which provide researchers with avenues for future research in this area alongside a need for each construct to be examined in relation to choking behavior in sport.